Draft of the Report of the United Nations Special Committee on Recent Events in Hungary - Héderváry, Claire de (1957)
Records of this digital collection were assembled to document the work of the UN Special Committee on the Problem of Hungary established on January 10, 1957 by the United Nations General Assembly for the purpose of investigating the 1956 Hungarian revolution. Principal contributor(s): László Hámori; Council of Europe Draft summary of the report of the Special Committee, highlighting the most important conclusions.